O impacto do reconhecimento de ativos fiscais diferidos na situação econômica e financeira das empresas - Webber, Fabiano Lima (Universidade do Vale do Rio do Sinos, 2009)
This research examined the impact of the recognition of deferred tax assets (AFDs) in rates of current liquidity, general liquidity, debt and profit of the inheritance of 36 companies that are part of the level of governance corporative from BOVESPA, called "New Market" with data from accounting statements for the period from 2006 to 2008. The indices were calculated without consideration and with consideration of deferred tax assets in these reported demostrations. The approach of the study is quantitative, as the aims; the research is descriptive, in regard about technical procedures; it is documentary. It was verified that the "t" test, that the recognition of AFDs has statistically significant impact on liquidity and debt. Additionally, trying to explain the different levels of recognition of AFDs in the sample, it was applied the test of correlation and dependency analysis through multiple regression. The results showed no significant relationship between the level of recognition AFDs and the explanatory
Keywords: reconhecimento de ativos; situação econômica; situação financeira; ativos fiscais diferidos; economical situation; financial situation; recognition of assets; deferred tax assets; Ciências Sociais Aplicadas